HUBUNGAN ANTARA AKTIVITAS PEMBELAJARAN BERBASIS STEAM DENGAN KUALITAS KEMANDIRIAN ANAK USIA DINI DI KELOMPOK B RA AL-KAUTSAR KOTA BANDUNG - Handayani, Diana; Hayati, Tuti; Nurdiansyah, Nano (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
The results of the preliminary study in Group B RA Al-Kautsar show that, there is a gap between the high STEAM-based learning activity and the quality of independence in some children. On the one hand, when carrying out STEAM-based learning activities children are motivated to learn independently, confidently. However, on the other hand there are some children who are still lacking in developing the quality of their independence. This situation can be seen when the child conveys the phrase